Extent of secondary intraventricular hemorrhage is an independent predictor of outcomes in intracerebral hemorrhage: data from the Helsinki ICH Study. Issue 4 (12th January 2015) - Mustanoja, Satu; Satopää, Jarno; Meretoja, Atte; Putaala, Jukka; Strbian, Daniel; Curtze, Sami; Haapaniemi, Elena; Sairanen, Tiina; Niemelä, Mika; Kaste, Markku; Tatlisumak, Turgut
<x xml:space="preserve">Abstract</x> Background Intraventricular hemorrhage is a severe subtype of intracerebral hemorrhage associated with high mortality and poor outcome. Aim We analyzed various intraventricular hemorrhage scores at baseline to find common parameters associated with increased mortality. Methods Consecutive intracerebral hemorrhage patients treated in Helsinki University Central Hospital during 2005–2010 were included in the Helsinki Intracerebral Hemorrhage Study registry and analyzed for three‐month mortality. Results After excluding lost‐to‐follow‐up patients, 967 intracerebral hemorrhage patients were included, out of whom 398 (41%) had intraventricular hemorrhage. Intraventricular hemorrhage patients, compared with nonintraventricular hemorrhage patients, had lower baseline Glasgow Coma Scale [median 12 (IQR 6–15) vs. 15 (13–15); P < 0·001] and higher National Institutes of Health Stroke Scale [18 (10–27) vs. 7 (3–14); P < 0·001] scores; larger intracerebral hemorrhage volumes [17 ml (7·2–42) vs. 6·8 (2·4–18); P < 0·001] and more often hydrocephalus (51% vs. 9%; P < 0·001); and higher mortality rates (54% vs. 18%; P < 0·001). In multivariable analysis, the presence of intraventricular hemorrhage was independently associated with mortality [OR 2·05 (95% CI 1·36–3·09)] when adjusted for well‐known prognostic factors of intracerebral hemorrhage, i.e. age, gender, baseline National Institutes of Health Stroke Scale, intracerebral hemorrhage volume, infratentorial location, and etiology. Conclusions The presence of intraventricular hemorrhage was independently associated with increased mortality, and all the intraventricular hemorrhage scores were strong predictors of three‐month mortality.